The Influence of Learningworkload on Schoolchildren Health/Development and Teaching Motivation (Global Journal of Human-Social Science, 2023)
Based on Lithuanian and foreign scientific pedagogical and psychological literature and normative state documents the article identifies a disproportionate educational workload depending on the age of children The influence of workload on schoolchildren s motivation and health development is examined Exhaustion of the nervous system due to an irrational daily routine reasons for noncompliance with the daily routine and lack of healthy sleep due to an inadequate amount of homework exceeding the hygiene norms of the student s safe mental work are identified The author analyses the learning workload motivation to learn and health problems in the development of children s social competencies This paper also examines the education system s shortcomings lesson schedule methodology didactics amount and complexity of homework corresponding to the age of the schoolchildren which depend on the health development of students and the motivation for learning and the desire to attend school The survey results of students teachers and parents are being presented
Keywords: learning workload/motivation; desire to attend school; child/student health/development; sleep/adolescence